Second Time’s the Charm: An Empirical Examination of the Benefits and Potential Drawbacks of Repeat Legal Externships - Carolyn Young Larmore (Washington University Journal of Law and Policy, 2023)
Law schools offer externships to give students real world experience that cannot be taught in the classroom. We encourage field supervisors to provide students with a variety of assignments of an increasingly challenging nature. And our students perform well, practicing important legal skills and impressing their supervisors. So, what happens when a student has such a good experience that they are asked to stay on another semester? Are there more lessons to be learned, or other benefits to be had, from another four months of fieldwork at the same placement? Or should law school faculty require students to find a new experience to expand their legal horizons? This article takes a first-of-its-kind empirical approach to answering these questions. The author undertook three surveys—of externship faculty, field supervisors, and students—as well as an analysis of several years’ worth of externship program data, to shed light on the pros and cons of allowing students to repeat a legal externship at the same placement. What the surveys and program data uncovered was that, while repeat externships are met with suspicion by more than half the law schools in the country, externship field supervisors and students view them as an opportunity to provide more significant and challenging work, further mentoring, and a path toward full-time, post-graduate employment. Moreover, more than ninety percent of supervisors of repeat externs found that their students’ legal skills increased during the second externship period, a figure mirrored by the post-externship self-assessment of repeat externs as compared to first timers. Finally, while some drawbacks to repeat externships were discovered—namely a small percentage of post- graduation job offers that did not materialize, as well as a feeling of being “stuck” in a certain practice area—the author posits that these shortcomings are better addressed with placement screening and student counseling than by a blanket ban of repeat externships.
Keywords: externships; supervisors; externs; legal skills; legal education; repeat externships; program; classroom; law school; fieldwork; experience; legal experience; placements; empirical approach; surveys